1987
DOI: 10.2170/jjphysiol.37.425
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of arteriovenous anastomoses to vasoconstriction induced by local heating of the human finger.

Abstract: Blood flows in the finger were measured simultaneously by laser Doppler flowmetry and by venous occlusion plethysmography in a warm environment (35°C, 40% RH). One hand was immersed in a water bath the temperature of which (TW) was raised every 10 min by steps of 2°C from 35 to 43°C, while the other hand was kept immersed in water at 35°C. Finger blood flow in the heated hand (BF) measured with venous occlusion plethysmography was significantly lower than that in the control hand (BFI) at TW of 39-41°C. At TW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 13 publications
0
11
1
1
Order By: Relevance
“…The high S m O 2 value of 92.6±3.7% observed for the fingertip of volunteers at rest agreed well with the oxygen saturation value of 92±2.6% reported by Caspary et al [11] who also conducted the similar experiment. This is due to the presence of Arteriovenous anastomoses (AVAs) that are available in abundance in acral (fingertip) than non-acral skin (back of the hand) [12]. This result in a lower S m O 2 with mean value of 39.8±6.85% observed in this work for the back of the hand experiment.…”
Section: Discussionmentioning
confidence: 59%
“…The high S m O 2 value of 92.6±3.7% observed for the fingertip of volunteers at rest agreed well with the oxygen saturation value of 92±2.6% reported by Caspary et al [11] who also conducted the similar experiment. This is due to the presence of Arteriovenous anastomoses (AVAs) that are available in abundance in acral (fingertip) than non-acral skin (back of the hand) [12]. This result in a lower S m O 2 with mean value of 39.8±6.85% observed in this work for the back of the hand experiment.…”
Section: Discussionmentioning
confidence: 59%
“…This laser Doppler flowmetry has been shown to correlate well with many of the conventional methods used to assess peripheral blood flow (STERN et al, 1977(STERN et al, , 1979ENGELHART and KRISTENSEN,1983;LARRABEE et a!.,1983;SMITs et a!., 1986). However, we have observed previously that local heating of the hand from 37 to 41 ~C in a warm environment caused a reduction of finger blood flow when measured by venous occlusion plethysmography and, in contrast, a continued increase of finger blood flow when measured by laser Doppler flowmetry (PERIFLUX PF-ld) (NAGASAKA et a!., 1987). Thus the pattern of blood flow changes in the human finger in response to local heating moved in opposite directions, as measured by laser Doppler flowmetry and venous occlusion plethysmography.…”
Section: Discussionmentioning
confidence: 65%
“…Taken together with findings obtained from the sheep's hindleg [14] and dog's tongue [32], evidence suggests that the AVA's are the vascular compartments responsible for this heatinduced vasoconstriction in the finger. NAGASAKA et al [26] demonstrated the effects of 2 °C-stepwise increases in local temperature from 35 to 43°C on the superficial vessels of the finger. As described above, finger blood flow in the heated hand measured with venous occlusion plethysmography was significantly lower than that in the control hand at TW of 39-41 °C.…”
Section: C) Vascular Compartments Responsible For the Heat-induced Vamentioning
confidence: 99%
“…This has been evaluated by measuring finger blood flows with two different laser Doppler flow-probes [26]. The laser Doppler-probes consist of parallel exciting and receiving optic fibers separated at a certain distance.…”
Section: C) Vascular Compartments Responsible For the Heat-induced Vamentioning
confidence: 99%
See 1 more Smart Citation